2020
DOI: 10.3390/ijerph17145030
|View full text |Cite
|
Sign up to set email alerts
|

Organophosphate Pesticide Exposure and Breast Cancer Risk: A Rapid Review of Human, Animal, and Cell-Based Studies

Abstract: Background: Organophosphate pesticides (OPs) are one of the most commonly used classes of insecticides in the U.S., and metabolites of OPs have been detected in the urine of >75% of the U.S. population. While studies have shown that OP exposure is associated with risk of neurological diseases and some cancers, the relationship between OP exposure and breast cancer risk is not well understood. Methods: The aim of this rapid review was to systematically evaluate published literature on the relationship betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(17 citation statements)
references
References 75 publications
0
17
0
Order By: Relevance
“…It can be noted that IARC classified some organophosphate pesticides as "probably carcinogenic to humans" (Group 2A) and "possibly carcinogenic to humans" (Group 2B) 10 . Endocrine disruption potential of pesticides has also been described in toxicological studies and recently in a review by Yang et al 7,60 , and could be particularly involved in hormone-dependent breast carcinogenesis, as some pesticides are known to mimic estrogen functions 57,61 . Indeed, azole fungicides, including imazalil, for which we found high correlations with NMF Component 1, have been related to inhibition of estrogen biosynthesis in some studies 62 .…”
Section: Discussionmentioning
confidence: 96%
“…It can be noted that IARC classified some organophosphate pesticides as "probably carcinogenic to humans" (Group 2A) and "possibly carcinogenic to humans" (Group 2B) 10 . Endocrine disruption potential of pesticides has also been described in toxicological studies and recently in a review by Yang et al 7,60 , and could be particularly involved in hormone-dependent breast carcinogenesis, as some pesticides are known to mimic estrogen functions 57,61 . Indeed, azole fungicides, including imazalil, for which we found high correlations with NMF Component 1, have been related to inhibition of estrogen biosynthesis in some studies 62 .…”
Section: Discussionmentioning
confidence: 96%
“…The authors proposed that EBV presence affects the response of BC cells to nicotine [ 103 ]. In addition, it has been shown that organophosphate pesticides such as malathion or parathion are related to BC by in vitro and in vivo approaches [ 104 , 105 , 106 ]. Notably, it was reported that chlorpyrifos, an organophosphate pesticide, can promote EBV lytic cycle activation by promoting BZLF1 expression by oxidative stress in a lymphoblastoid cell line.…”
Section: Ebv In Breast Cancer: Potential Mechanismsmentioning
confidence: 99%
“…On the other hand, estradiol metabolism may result in quinone derivatives, which directly replace base pairs from DNA through depurination, and can also alter the DNA repairing process (109)(110)(111). It has been reported that estrogens are potent mammary tumor promoters influencing post-initiation events through epigenetic mechanisms.…”
Section: Parathion and Malathion Induce Metabolic Alterationsmentioning
confidence: 99%